KONSTRUKSI PENGETAHUAN PETANI ORGANIK DESA WATES KABUPATEN TULUNGAGUNG - Khotimah, Aidah Chusnul; Jannah, Raudlatul (Jurnal ENTITAS SOSIOLOGI, 2016)
Abstract The shift of conventional farmers in Wates Village to an organic farming system is a long process. The fairly long transition process is due to the different treatments of both conventional and organic farming systems. The difference is from seeding to harvesting process which requires special, different treatment from conventional farming. Various obstacles must be passed by farmers to switch to organic farming systems. This research focuses on the construction of knowledge of organic farming which makes the farmers switch towards organic farming systems. The research used the social construction theory of Petter L. Berger and Thomas Luckmann that would examine the construction of knowledge about organic farming among farmers in Wates Village. The research used a constructivist approach. The informants were determined by purposive sampling. Furthermore, data were collected through observation, interview, and documentation. The results showed that the organic rice farmers in Wates village experienced a construction process through knowledge of farming systems. The knowledge was from a variety of sources including books, the Agricultural Extension Agency, and farmer groups. The role of governments, NGOs and civil society greatly helped the transition process towards organic farming systems among farmers in Wates Village. Objective reality and subjective reality were experienced by farmers in Wates Village in the transition process. Keywords: Construction, Science, Farmers, Organic Rice